Search for η mesic 3He with the WASA-at-COSY facility in the pd→3He2γ and pd→3He6γ reactions - Adlarson, P.; Augustyniak, W.; Bardan, W.; Bashkanov, M.; Bass, S. D.; Berłowski, M.; Bondar, A.; Büscher, M.; Calén, H.; Ciepał, I.; Clement, H.; Czerwiński, E.; et al. (Physics Letters B, 2020)
We report on the experimental search for the bound state of an η meson and He3 nucleus performed using the WASA-at-COSY detector setup. In order to search for the η-mesic nucleus decay, the pd→3He2γ and pd→3He6γ channels have been analysed. These reactions manifest the direct decay of the η meson bound in a He3 nucleus. This non-mesonic decay channel has been considered for the first time. When taking into account only statistical errors, the obtained excitation functions reveal a slight indication for a possible bound state signal corresponding to a 3He-η nucleus width Γ above 20 MeV and binding energy Bs between 0 and 15 MeV. However, the determined cross sections are consistent with zero in the range of the systematic uncertainty. Therefore, as final result we estimate only the upper limit for the cross section of the η-mesic He3 nucleus formation followed by the η meson decay which varies between 2 nb and 15 nb depending on possible bound state parameters.
CRIS-Team Scopus Importer:2020-01-24
Keywords: η meson; η-mesic nuclei